Pengukuran Tingkat Kualitas Pelayanan Pit-Stop Kopi Gresik - Narto, Narto (Universitas Serang Raya, 2019)
Coffee Pit Stop is one of the coffee shops in the city of Gresik, with its segmentation of consumers being middle and lower markets at prices that are very affordable for every community. Based on the initial survey, some complaints were felt by the customer, including seating for only one person so that if they came together with a large number they had to adjust their place first, the service was less representative; the taste variants were limit to each menu offered. This study aims to measure customer satisfaction by using the Servqual, IPA, and PGCV method with 100 respondents. The results showed that there were three attributes in quadrant A namely P4 very complete support facilities with PGCV values of 5.99, P5 wide and safe parking area with a PGCV value of 5.54, P10 immediately providing the right service according to customer desires with amount PGCV is 5.50. The corrective action taken to improve service quality is to carry out routine cleaning of the supporting facilities owned by Gresik Pit Stop. Suitable parking arrangements by parking officers must always consider so that the effectiveness of land use can be maximized, and the waiter must pay attention to the accuracy and speed in serving customers so that customer satisfaction will be creating.